Influencer representation in Tokopedia advertising: Tokopedia squad - Benjamin , Johanes; Okta Wibowo, Tangguh (Jurnal Komunikasi, Sains dan Teknologi, 2023)
The advertisement uploaded by Tokopedia entitled Tokopedia Squad describes several influencers who are the solution for Indonesian people to obtain products and services that are useful for everyday life. There are sebelas influencers used in the advertisement. However, in this study the researcher analyzed 5 influencers in the advertisement. The purpose of this study is to determine the representation of the use of these influencers in Tokopedia Squad advertisements. This research uses a qualitative approach with a descriptive type of research to explain how these influencers have their own meaning and purpose in this advertisement. This study also uses representation theory with semiotic analysis techniques from Charles Sanders Peirce with sign, object, and interpretant. The research results show that the five influencers describe the categories and features owned by Tokopedia with the aim of attracting awareness from each market owned by these influencers. Tokopedia uses them to showcase the features or categories of the Tokopedia application, naturally tailored to each influencer's intended market or audience.